Identification of 3,3'-O-dimethylellagic acid and apigenin as the main antiplasmodial constituents of Endodesmia calophylloides Benth and Hymenostegia afzelii (Oliver.) Harms - Rodrigue Keumoe; Jean Garba Koffi; Darline Dize; Patrick Valère Tsouh Fokou; Joseph Tchamgoue; Lawrence Ayong; Bruno Lenta Ndjakou; Norbert Sewald; Bathelemy Ngameni; Fabrice Fekam Boyom (BMC, 2021)
Abstract Background Endodesmia calophylloides and Hymenostegia afzelii belong to the Guttiferae and Caesalpiniaceae plant families with known uses in African ethno-medicine to treat malaria and several other diseases. This study aimed at identifying antiplasmodial natural products from selected crude extracts from H. afzelii and E. calophylloides and to assess their cytotoxicity. Methods The extracts from H. afzelii and E. calophylloides were subjected to bioassay-guided fractionation to identify antiplasmodial compounds. The hydroethanol and methanol stem bark crude extracts, fractions and isolated compounds were assessed for antiplasmodial activity against the chloroquine-sensitive 3D7 and multi-drug resistant Dd2 strains of Plasmodium falciparum using the SYBR green I fluorescence-based microdilution assay. Cytotoxicity of active extracts, fractions and compounds was determined on African green monkey normal kidney Vero and murine macrophage Raw 264.7 cell lines using the Resazurin-based viability assay. Results The hydroethanolic extract of H. afzelii stem bark (HasbHE) and the methanolic extract of E. calophylloides stem bark (EcsbM) exhibited the highest potency against both Pf3D7 (EC50 values of 3.32 ± 0.15 μg/mL and 7.40 ± 0.19 μg/mL, respectively) and PfDd2 (EC50 of 3.08 ± 0.21 μg/mL and 7.48 ± 0.07 μg/mL, respectively) strains. Both extracts showed high selectivity toward Plasmodium parasites (SI > 13). The biological activity-guided fractionation led to the identification of five compounds (Compounds 1-5) from HasbHE and one compound (Compound 6) from EcsbM. Of these, Compound 1 corresponding to apigenin (EC50 Pf3D7, of 19.01 ± 0.72 μM and EC50 PfDd2 of 16.39 ± 0.52 μM), and Compound 6 corresponding to 3,3'-O-dimethylellagic acid (EC50 Pf3D7 of 4.27 ± 0.05 μM and EC50 PfDd2 of 1.36 ± 0.47 μM) displayed the highest antiplasmodial activities. Interestingly, both compounds exhibited negligible cytotoxicity against both Vero and Raw 264.7 cell lines with selectivity indices greater than 9. Conclusions This study led to the identification of two potent antiplasmodial natural compounds, 3,3'-O-dimethylellagic acid and apigenin that could serve as starting points for further antimalarial drug discovery.